Model Implementasi Bioenginering Sebagai Upaya Mitigasi Longsor : (Kajian di Lokasi Rawan Longsor Desa Jatiradio Kecamatan Cililin Kabupaten Bandung Barat) - Hasmana Soewandita (Agency for the Assessment and Application of Technology / Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Landslide is one of the high frequency disasters that occur in Indonesia. The incident recurs every year with a different location. The fact that landslide hazards are used intensively for agricultural cultivation due to economic considerations. One of the efforts to mitigate this disaster is the Bioenginering implementation approach. Bioenginering activity is the application of landslide hazard area management by managing plants / vegetation. The purpose of this research is to implement a vegetative technology implementation model as an effort to mitigate landslides. Bioenginering implementation is designed with a combination of ecological and socio-economic approaches. The results of this combination are consulted with the affected community and consider various vegetation alternatives. The selected vegetation not only has an ecological function but also an economic function. With these considerations, a vegetation design is obtained with a combination of upper strata (trees), middle and lower strata. For the upper strata it is recommended to plant Petai (Parkia speciosa) and Durian (Durio zibenthinus), for the middle strata, namely Coffee (Coffea arabica) and lower strata plants are pineapple (Ananas commocus). The combination of plants such as the implementation at the field level will be accepted by the farming community, because every certain period of time the farmers will be able to harvest their crops without having to remove the plants or cut down the plants. Maintaining the level of land cover and land use has implications for maintaining the stability of soil moisture conditions which in turn can reduce the threat of landslides in landslide hazard areas.